Synthesis and characterization of iron-manganese oxide adsorbents from actual drinking water treatment residuals for hexavalent chromium removal - Sumalinog, Mario Jose R. II (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Waste streams are discharged from electroplating units and similar industrial operations containing high concentrations of toxic hexavalent chromium *Cr VI) ions. In this study, novel adsorbents for Cr (VI) removal were synthesized by coating sand with drinking water treatment (DWT) residuals. The effects of the residual-coated sand (RCS) synthesis parameters, namely: acid concentration, acid type and ratio, ultrasonication time, and heating duration, to the adsorption capacities of RCS were investigated. Compared to adsorbents treated with pure acid solutions, acid treatment using dual-acid solutions yielded lower adsorption capacities. The RCS adsorption capacity increased with ultrasonication time and heating duration. The highest adsorption capacity (641.2 mg/kg) was obtained by RCS synthesized using the following conditions: 0.5% w/w H₂SO₄, 30 min ultrasonication to the Freundlich isotherm (R² = 0.9607). Energy Dispersive X-ray (EDX) analysis confirmed the predominance of Fe and Mn oxides on RCS surface while Fourier Transform Infrared Spectroscopy (FTIR) spectra revealed the involvement of these metal oxides in the adsorption of Cr (VI) ions. The findings of this study demonstrated the potential of RCS in removing Cr (VI) for industrial wastewaters.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Adsorption; Water -- Purification -- Chromium removal